Failure of remission induction by glucocorticoids alone or in combination with immunosuppressive agents in IgG4-related disease: a prospective study of 215 patients - Wang, Liwen; Zhang, Panpan; Wang, Mu; Feng, Ruie; Lai, Yamin; Peng, Linyi; Fei, Yunyun; Zhang, Xuan; Zhao, Yan; Zeng, Xiaofeng; Zhang, Fengchun; Zhang, Wen (Arthritis research & therapy, 2018)
The aim of this study was to assess the outcomes of remission induction in patients with IgG4-related disease (IgG4-RD) in our cohort, and to investigate the characteristics, prognosis, and risk factors in the patients failed of remission induction. We prospectively enrolled 215 newly diagnosed patients with IgG4-RD, who were initially treated with glucocorticoid (GC) alone or in combination with immunosuppressive agents (IM), and had at least 6 months of follow up. The therapeutic goals of remission induction were defined as fulfilling each of the following after the 6-month remission induction stage: (1) ≥ 50% decline in the IgG4-RD responder index (RI); (2) GC tapered to maintenance dose; and (3) no relapse during GC tapering. The patients not achieving the therapeutic goals were considered to have failed of remission induction. There were 26 patients in our cohort who failed of remission induction, including 16 (20.8%) on GC monotherapy, and 10 (7.2%) on combination therapy comprising GC and IM. The lacrimal gland and lung were most common sites of remission induction failure. Among the patients who relapsed during remission induction stage, 52.9% had secondary relapse during follow-up. Eosinophilia, higher baseline RI, more than five organs involved and dacryoadenitis were risk factors for remission induction failure with GC monotherapy, and the incidence of remission induction failure was 71.4% in the patients with more than three risk factors. After 6-month treatment, the patients who failed of remission induction had significantly higher erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and IgG4. In our cohort, 20.8% of patients failed of remission induction with GC monotherapy, while 7.2% of patients failed of remission induction with combination therapy comprising GC and IM.